A Systematic Review and Meta-analysis of the Effect of Oral Exercises on Masticatory Function. (May 2022) - Shu, X.; He, S.; Lo, E.C.M.; Leung, K.C.M.
The aim of the current systematic review was to summarize and to evaluate the available information on the effectiveness of oral exercise in improving the masticatory function of people ≥18 y. Electronic databases (Medline, Embase, CENTRAL) and gray literatures were searched (up to December 2020) for relevant randomized and nonrandomized controlled clinical trials. Two reviewers independently conducted the study selection, data extraction, and quality assessments. Meta-analysis was conducted for the comparison of bite force and masticatory performance using mean difference (MD) and standardized mean difference (SMD), respectively. GRADE (Grading of Recommendations Assessment, Development, and Evaluation) assessment was adopted for collective grading of the overall body of evidence. Of the 1, 576 records identified, 18 studies (21 articles) were included in the analysis. Results of meta-analysis indicated that oral exercise could significantly improve the mean bite force of the participants (parallel comparison: MD, 41.2; 95% CI, 11.6–70.7, P = 0.006; longitudinal comparison: MD, 126.5; 95% CI, 105.2–144.9, P < 0.001). However, the improvement in masticatory performance was not significant (parallel comparison: SMD, 0.11; 95% CI, –0.20 to 0.42, P = 0.48; longitudinal comparison: SMD, 0.4; 95% CI, –0.11 to 0.91, P = 0.13). Results of meta-regression showed that greater improvements in bite force can be achieved among younger adults and with more intensive exercise. Chewing exercise is the most effective oral exercise, followed by clenching exercise, while simple oral exercise may not have a significant effect. Based on the results of the meta-analysis and GRADE assessment, a weak recommendation for people with declined masticatory function to practice oral exercise is made.